Beginnings of modern history studies in Malaysia: a bibliometric study of the journal of the historical society, Universiti Malaya, Kuala Lumpur (1960-1969/1970) - Mohd Noor Merican, Ahmad Murad; Akgun, Tayfun (Department of History Faculty of Arts and Social Sciences Universiti Malaya, 2023)
The Journal of the Historical Society, Universiti Malaya, Kuala Lumpur, is the first example of academic and university-based historical journals that appeared after Malaya attained independence from the British Empire in 1957. It was annually published between 1960 and 1969/1970. The main objective of the journal was to disseminate and encourage historical studies on Southeast Asia in general and Malaysia in particular. This study bibliometrically examines the Journal of the Historical Society in terms of the number of articles, the types of articles, their subject areas, author productivity, and authorship patterns. The study has found that 100 articles, 10 book reviews and 1 poem were published in a total of 10 issues of the journal between 1960 and 1969/70. A large number of articles are closely related to history; the rest are to international relations (IR), politics and archaeology. The journal gave priority to historical studies on Malaysia. Political history and historiography are predominant research areas among historians and history students in the 1960s. The number of English articles in the journal outnumbers that of Malay articles. All articles were written by a single author. The pattern of co-authorship did not exist in the journal.